2022
DOI: 10.1590/1807-1929/agriambi.v26n1p75-81
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability, stability and environmental stratification of genetically and nongenetically modified corn in the Cerrado

Abstract: Crop yield depends on interaction between genetic and environmental factors, making it essential to study adaptability, stability and environmental stratification in order to mitigate the effects of this interaction. Four experiments were conducted to assess competition between corn cultivars in the 2018/19 growing season, two in Paraíso do Tocantins and two in Palmas, with sowing performed on November 5, 2018 and January 15, 2019. Cultivar-environment interaction was analyzed in genetically modified (GM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The joint variance analysis showed significant effects for genotype, environment, and G×E interaction for all four traits (Table 4). Similar results for G×E interactions were observed by CHANGIZI et al (2014), BUSANELLO et al (2015), PRADO et al (2016), GAMI et al (2017), FARIA et al (2017), SANTOS et al (2018a, PINTO et al (2019), BERNINI & GUIMARÃES (2020), Eckardt et al (2022), andSHOJAEI et al (2022) in maize traits, demonstrating the necessity of evaluating genotypes over multiple years, seasons, or cultivation locations.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The joint variance analysis showed significant effects for genotype, environment, and G×E interaction for all four traits (Table 4). Similar results for G×E interactions were observed by CHANGIZI et al (2014), BUSANELLO et al (2015), PRADO et al (2016), GAMI et al (2017), FARIA et al (2017), SANTOS et al (2018a, PINTO et al (2019), BERNINI & GUIMARÃES (2020), Eckardt et al (2022), andSHOJAEI et al (2022) in maize traits, demonstrating the necessity of evaluating genotypes over multiple years, seasons, or cultivation locations.…”
Section: Resultssupporting
confidence: 74%
“…Several authors have used the Eberhart and Russel (1966) method for different traits, including grain yield (CHANGIZI et al, 2014;BUSANELLO et al, 2015;PRADO et al, 2016;FARIA et al, 2017;PINTO et al, 2019;BERNINI & GUIMARÃES, 2020;ECKARDT et al, 2022;SHOJAEI et al, 2022), oil content (SANTOS et al, 2018a, and phenological and morphological traits (e.g., male and female flowering and plant and ear height) (BERNINI & GUIMARÃES, 2020;GAMI et al, 2017;PRADO et al, 2016). Nonetheless, no adaptability and stability studies were reported using the EBERHART & RUSSEL (1966) method for tassel traits, which are extremely important when selecting and recommending genotypes.…”
Section: Introductionmentioning
confidence: 99%